Deep crustal structure and estimation of moho in the lhasa terrane of central tibet (2008)
Seismic attributes analysis is applied to INDEPTH II seismic profiles to develop a better understanding of the deep crustal structure and geodynamics of the Lhasa Terrane in the central Tibet area. Analyses indicate that the frequency anomalies are obtained over the range in between 0-30 Hz. Some area of the analyzed traces of the seismic profiles have shown dominated frequency anomaly approximately 10 Hz with little amount of other frequencies. The variation of frequency anomaly is shown to be the indication of theMoho depth of the area. EstimatedMoho depths are found very irregular and varying from20 kmto more than 136 km. The crust is thinner in southern, northern and eastern parts of the area while it is thicker in the western part having asymmetric nature in the central part. This variation might be the result of the complicated tectonic process of the Indian and Eurasian plates. Vertically downward pocket like frequency distributions and similar type frequency distributions at near and far depth are also observed in one of the analyzed sections. It might be indication of uprised asthenospheric matter which exchanged with lithosphere in subduction zones related to the multiple crustal uprising.